THE INFLUENCE OF MADRASAH HEAD LEADERSHIP AND PARENTAL SUPPORT ON STUDENT ACADEMIC ACHIEVEMENT AT MAN 2 BULUKUMBA - Nursinta, Nursinta; Abidin, Munirul (Idaarah: Jurnal Manajemen Pendidikan, 2024)
Student academic achievement serves as a crucial measure of educational success, shaped by various internal and external factors. A significant element in this context is the influence of the madrasa head’s leadership in fostering a supportive learning environment, coupled with parental support that encompasses emotional backing, material assistance, and active engagement in school activities. This study seeks to examine how school leadership and parental support impact the enhancement of students' academic achievement at MAN 2 Bulukumba. Using a quantitative approach with a non-experimental design, this research involved 103 students selected through stratified random sampling techniques. Data were gathered using questionnaires that focused on three primary variables: madrasa head’s leadership, parental support, and student academic achievement. The data analysis was carried out using multiple linear regression via SPSS 27. The results show that madrasa head leadership (X1) has a positive and significant effect on student academic achievement, with a significance value of 0.026 (p < 0.05) and a t-value of 2.263. Parental support (X2) also has a positive and significant effect, with a significance value of 0.010 (p < 0.05) and a t-value of 2.618. Overall, these two variables have a significant simultaneous effect on student academic achievement, with an F-value of 10.235 (p = 0.001). This study concludes that the synergy between the madrasa head’s leadership and parental support positively impacts the improvement of student academic achievement.